Causes and control to lateral displacement of the main girder in the super-long-span cable-stayed bridge with transverse asymmetry dead load. (March 2022) - Zhang, Jinxiang; Zhang, Mingjin; Jiang, Xulei; Yuan, Renan; Yu, Jisheng; Zhou, Yuanzhou; Qin, Shunquan
Abstract: In the densely populated large cities, to save valuable land resources and fit the plane alignment of the approach bridge at two ends of the main bridge, the long-span Rail-cum-Road cable-stayed bridge is arranged on the same deck with the lateral asymmetric layout. This makes the transverse secondary dead load of the main girder asymmetric and the mechanical characteristics different from the conventional cable-stayed bridge. In this paper, firstly, several measures to realize the ideal vertical alignment of the main girder for such cable-stayed bridges were analyzed theoretically, and the mechanical characteristics of the main girder via the measure of asymmetrical cable force were mainly explored. Then, taking the Changzhou-Taixing Yangtze River bridge as a typical example, a simplified mechanical model was proposed to calculate the lateral displacement of the main girder and was compared with the finite element model (FEM) of the whole bridge. Finally, according to the mechanical model, the control measures to lateral displacement of the main girder were discussed. The results show that the unbalanced longitudinal and lateral components corresponding to the asymmetric cable force lead to the main girder to deviate railway side and the highway side, respectively, and the corresponding variance value of lateral displacement is not significant, which greatly reduces the lateral shift effect of the main girder. Furthermore, the simplified mechanical model can effectively calculate the lateral displacement of the main girder and study the control measures for displacement. The conclusions of this study can provide a basis for further design of the same type of bridge.